Technical and Economic Assessment of Tidal Barrage Power Plant at Ambon Bay, Indonesia Using Life Cycle Cost Analysis - Achmad Nawawi; Zainal Arifin; Ali Herman Ibrahim (TIN: Terapan Informatika Nusantara, 2026)
Ambon Bay in Maluku Province possesses significant tidal energy potential due to its semi-enclosed morphology and favorable tidal characteristics, making it a promising site for tidal barrage power development in Eastern Indonesia. This study aims to evaluate the technical potential and economic feasibility of a tidal barrage power plant in Ambon Bay. Tidal energy potential was estimated using harmonic tidal data obtained from pasanglaut and the Marine Observation Research Agency (BROL), followed by energy conversion analysis based on tidal range and basin characteristics. The technical assessment was conducted using an analytical approach derived from hydrodynamic principles and benchmarked against existing tidal barrage systems. Economic feasibility was evaluated using the Life Cycle Cost (LCC) method, incorporating capital expenditure, operational costs, and Levelized Cost of Energy (LCOE), along with Net Present Value (NPV) analysis. The results indicate that Ambon Bay has a theoretical tidal energy potential of 31.05 GWh per year. A proposed 7 MW tidal barrage system could generate approximately 11.69 GWh annually with a capacity factor of 18.9%. The estimated capital cost is IDR 255,231,448 per kW, with an LCOE of IDR 15,324 per kWh. The economic analysis yields an NPV of -IDR 1,294,358,382,098.43, indicating that the project is not economically feasible under current conditions. These findings highlight that, despite its considerable technical potential, the development of tidal barrage power in Ambon Bay requires cost reduction strategies, policy support, or technological optimization to achieve economic viability.